2011
DOI: 10.1007/s10765-011-0978-y
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Viscosity Measurements of 1,1,1,2-Tetrafluoroethane

Abstract: Viscosity measurements have been carried out with a falling-cylinder instrument in the compressed liquid and supercritical regions of the hydrofluorocarbon 1,1,1,2-tetrafluoroethane (R134a). A highly pure sample was used. The measurement region at temperatures from 293.15 K to 438.15 K with pressures from 10 MPa to 400 MPa extends the existing data range substantially. With estimated uncertainties of 3.5 % for viscosity, the greater of 1 MPa or 0.5 % for pressure, and 0.4 K for temperature, the new results can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 33 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…97 The capability of this type of formulation was applied in several other reference correlations 24, 98102 but it was shown that the singularity of the viscosity for V → V 0 leads to significant overpredictions even at modest extrapolations. 103 Therefore, free-volume terms were no longer considered in the present study.…”
Section: Formulation Conceptmentioning
confidence: 99%
“…97 The capability of this type of formulation was applied in several other reference correlations 24, 98102 but it was shown that the singularity of the viscosity for V → V 0 leads to significant overpredictions even at modest extrapolations. 103 Therefore, free-volume terms were no longer considered in the present study.…”
Section: Formulation Conceptmentioning
confidence: 99%
“…The viscosity of the neat refrigerant was not measured as part of this work. A slightly different instrument with a very slow falling ‘cup’ sinker is needed . Refrigerant viscosity seldom is much greater than 2 mPa·s under the conditions investigated here.…”
Section: Refrigerant Viscositiesmentioning
confidence: 99%
“…Refrigerant viscosity seldom is much greater than 2 mPa·s under the conditions investigated here. The viscosity measurements at 40°C, 75°C and 100°C on R134a reported in the literature were used here.…”
Section: Refrigerant Viscositiesmentioning
confidence: 99%
“…The viscosity of the refrigerant, R134a, which is 1,1,1,2-tetrafluoroethane, has been measured to pressures of 10 to 400 MPa in reference [17]. These data for 40, 75 and 100°C are shown in Figure 5 where the curves are a correlation fitted to the data.…”
Section: Refrigerantmentioning
confidence: 99%